Mechanisms of Variability Underlying Odor-Guided Locomotion - Tao, Liangyu; Bhandawat, Vikas (Frontiers in Behavioral Neuroscience, 2022)
Changes in locomotion mediated by odors (odor-guided locomotion) are an important mechanism by which animals discover resources important to their survival. Odor-guided locomotion, like most other behaviors, is highly variable. Variability in behavior can arise at many nodes along the circuit that performs sensorimotor transformation.; we review these sources of variability in the context of the Drosophila olfactory system. While these sources of variability are important, using a model for locomotion, we claim show that the mostanother important contributor to behavioral variability is the stochastic nature of decision-making during locomotion as well as the persistence of these decisions: Flies choose the speed and curvature stochastically from a distribution and locomote with the same speed and curvature for extended periods. This stochasticity in locomotion will result in variability in behavior even if there is no noise in sensorimotor transformation. Overall, the noise in sensorimotor transformation is amplified by mechanisms of locomotion making odor-guided locomotion in flies highly variable.